A theoretical review in evaluating the impact of traffic calming measures on the residential living environment - Rosli, Nur Shazwani; Kadar Hamsa, Abdul Azeez (2012)
A healthy living environment is vital to the positive lifestyle of a community. When traffic volumes or vehicle speeds in residential areas increase because of street design, social street activities are greatly reduced, and the feeling of well being in the affected neighbourhood is threatened. The cause of several accidents at the residential areas is also due to excessive speed caused mostly by the residents itself or persistent cut-through traffic, consequently leading to increase in noise pollution. Living environment in many residential areas has been deteriorating mainly because of these reasons. Addressing this issue, traffic calming measures is being perceived as a viable tool to reduce traffic speeds and accidents. The purpose of this research is to find the balance between traffic and environments by analysing the living environment through traffic calming measures. This paper highlights the literature background on traffic calming in Malaysia, impact of traffic calming to the residential living environment and other elements related to initial stage of study.